IgG and IgE antibodies to Chironomidae in asthmatic patients. - Yamashita, N (1987)
IgG antibodies to Chironomidae and its correlations to radioallergosorbent and skin reactions were examined with the aim of clarifying the relationship between asthma and Chironomidae. The level of specific IgG antibody in asthmatic patients (0.698 +/- 0.034, n = 104) was significantly greater than that in normal subjects (0.367 +/- 0.032, n = 52) (P less than 0.01). The specific IgG level was not correlated to skin reaction, nor to IgE RAST scores. Specific IgG1 and IgG4 levels in asthmatic patients were significantly greater than in control subjects (n = 14) (P less than 0.01).